Cervical cancer screening program in Indonesia: is it time for HPV-DNA tests? Results of a qualitative study exploring the stakeholders' perspectives - Fitriana Murriya Ekawati; Putri Listiani; Sri Idaiani; Jarir At Thobari; Firdaus Hafidz (BMC, 2024)
Abstract Objectives Cervical cancer is a significant public health concern in Indonesia, and effective screening methods are necessary to improve the detection and reduce mortality. This study aimed to explore the perspectives of high-level stakeholders involved in cervical cancer screening in Indonesia and whether the use of human papillomavirus-deoxyribonucleic acid (HPV-DNA) methods for cervical cancer screening is acceptable in Indonesian settings. Methods A qualitative research approach guided by realist evaluation was applied using focus group discussions (FGDs) between December 2021 and February 2022, conducted with stakeholders involved in cervical cancer screening in Indonesia. They were representatives of practitioners and policymakers involved in the screening, and were recruited through purposive recruitment. The data were analysed using inductive approach of thematic analysis. Results The analysis of two FGDs with 29 participants identified four main themes: (i) Visual inspection with acetic acid (VIA) method as the most common modality used for cervical cancer screening, (ii) the applied screening programs in the community, (iii) the perceived challenges on the screening program, such as limitations of the National Health Insurance benefits package and a lack of regulations regarding screening procedures, and (iv) the possibilities of HPV-DNA testing as another modality for cervical cancer screening. Incorporating HPV-DNA testing also needs to ensure the capacity of the workers and the readiness of healthcare facilities. Conclusion Although HPV-DNA testing is a promising modality, challenges on the cervical cancer screening in Indonesia remain on the coverage, accessibility of the tools in practice and the women's awareness towards the screening. Ultimately, the findings of this study would help inform policies to improve cervical cancer screening programs in Indonesia.